A Systematic Review of the Factors Associated with Cervical Cancer Screening Uptake among Women in Low and Middle-Income Countries - Elok Faradisa; Husna Ardiana; Diah Priyantini; Anis Fauziah; Inta Susanti (Universitas Airlangga, 2020)
Introduction: This review aims to explore the factors influencing cervical screening uptake among women in low and middle-income countries.Methods: The studies were systematically identified by searching electronic databases with the keywords “cervical cancer AND screening AND low of income countries AND middle of income countries.” The results consisted of 94 articles from Scopus, 100 articles from Science Direct, 74 articles from EBSCO, and 32 articles from PubMed. Following this, 16 studies were included in this systematic review with the inclusion criteria being quantitative or qualitative studies exploring the factors influencing woman’s cervical cancer screening uptake covering women in low- and middle- income countries, a clear study outcome and details on the associated factors, barriers to, and facilitators of screening uptake.Results: Knowledge about the disease and its prevention, knowing someone with cervical cancer and someone who has ever been screened, attitude and perception, husband approval, advice from the health care providers, and the distance to health care service were all important factors related to cervical cancer screening uptake in low and middle-income countries. The uptake of cervical cancer screening services was poor in low and middle-income countries. There is a need to strengthen the knowledge and awareness of woman related to cervical cancer screening services.Conclusion: The available evidence shows that intrapersonal and organizational factors are the most important factors that influence woman to undergo cervical cancer screening.